2014
DOI: 10.1111/ajsp.12058
|View full text |Cite
|
Sign up to set email alerts
|

Self-construal and students’ math self-concept, anxiety and achievement: An examination of achievement goals as mediators

Abstract: This study examines the role of self-construal in student learning by testing a mediation model: through math achievement goals, self-construal predicts math self-concept and anxiety, which further predict math achievement. A sample of 1196 students from 104 secondary classes in Singapore took a survey and a math achievement test. The results from multi-group structural equation modelling support measurement invariance and equal path coefficients in the mediation model between boys and girls. Interdependent se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 63 publications
3
29
0
1
Order By: Relevance
“…In the present study, a positive correlation was found between math self-concept and math achievement, and automatized math skills, which is in line with expectations based on previous studies (Atunes & Fontaine, 2007;Luo et al, 2014;McWilliams et al, 2013;Parker et al, 2013). The correlation was small for the math domains "measurement" and "relations", and medium for the domains "numbers" and "scale".…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the present study, a positive correlation was found between math self-concept and math achievement, and automatized math skills, which is in line with expectations based on previous studies (Atunes & Fontaine, 2007;Luo et al, 2014;McWilliams et al, 2013;Parker et al, 2013). The correlation was small for the math domains "measurement" and "relations", and medium for the domains "numbers" and "scale".…”
Section: Discussionsupporting
confidence: 93%
“…In line with expectations based on literature (Ashcraft & Krause, 2007;Ashcraft & Moore, 2009;Carey et al, 2016;Luo et al, 2014;Ramirez et al, 2013;Stankov et al, 2012;Wang et al, 2015), the current study found a negative correlation between math anxiety and math achievement. This correlation appeared to be only significant for the math domain "relations".…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Mathematics anxiety is commonly defined as a feeling of tension or fear that interferes with mathematics performance, and the correlations between mathematics anxiety and variables such as motivation and self-confidence in math are strongly negative (Ashcraft, 2002). Further, Mastery goal predicted negatively and performance goal did positively mathematics anxiety (Luo, Hogan, Tan, Kaur, Ng, & Chan, 2014). In the current study, we posit children and students' mathematics anxiety which reduce mathematics motivation.…”
Section: Mathematics Anxietymentioning
confidence: 99%